PENGARUH ENVIRONMENTAL SOCIAL AND GOVERNANCE, RETURN ON EQUITY, DAN EARNING PER SHARE TERHADAP HARGA SAHAM - Zuhrohtun, Zuhrohtun; Triana, Endah (Buletin Studi Ekonomi, 2023)
The purpose of this research is to examine and obtain empirical evidence on the impact of Environmental, Social, and Governance, Return On Equity, and Earnings Per Share as independent variables  on stock prices as the dependent variable . Environmental Social and Governance is measured using the content analysis method with reference to the ESG Reporting Guide 2.0 indicator published by the NASDAQ in 2019 . The data used is secondary data sourced from the Indonesia Stock Exchange's website and the official website of the related company. This study's population consists of mining sector firms listed on the Indonesia Stock Exchange (IDX) between 2019 until 2021. The sample for this research was taken using a purposive sampling method with adjusted sample criteria, and obtained a sample of 15 companies. This research uses descriptive statistical analysis, the classical assumption test, and hypothesis testing and multiple linear regression analysis. The results of this study prove that Environmental Social and Governance has an effect on stock prices, Return On Equity has an effect on stock prices, and Earning Per Share has an effect on stock price.